Dinamika identitas negara di kalangan mahasiswa multikultural - Mahardhika, Muhammad Fachry Putra (Maliki Interdisciplinary Journal, 2025)
This study discusses the dynamics of national identity among multicultural university students. Using a descriptive qualitative approach, it explores how students from various cultural backgrounds interpret the concept of national identity amid diverse values, norms, and social experiences. The findings indicate a negotiation process between local values, cultural origins, and Indonesian national identity. Interethnic interactions on campus may either reinforce or blur national identity, depending on social context and dominant discourse. This finding is important in understanding how higher education becomes a space for inclusive collective identity formation.